Utilization of Calophyllum inophyllum L. (Nyamplung) from Aceh as an Antioxidant Compound in Transparent Solid Soap - Liya Fitriyana; Rita Sunartaty (Jurnal Penelitian Pendidikan IPA, 2025)
Nyamplung (Calophyllum inophyllum L.) is a plant commonly found in coastal areas and lowlands. In Aceh, it is locally known as boeh beunot, a coastal species that grows easily and has various local names in different regions. This plant belongs to the Clusiaceae Lindl. Family and can be propagated both vegetatively (cuttings) and generatively (seeds). Nyamplung begins to bear fruit at the age of 5–20 years and can produce throughout the year, with peak harvest occurring in May–June. Fruit production can reach up to 20 tons/ha/year or approximately 250 kg/tree/year. In this study, nyamplung seeds originating from Aceh Province were utilized as a source of bioactive compounds for the formulation of transparent solid soap with antioxidant properties. The research stages included sample preparation (drying, peeling, and size reduction into powder), followed by extraction using the maceration method. Extraction optimization was carried out using the Response Surface Methodology (RSM) approach with Box-Behnken Design (BBD), involving three main factors (sample amount, extraction time, and solvent volume) at three levels (low, medium, and high). The obtained nyamplung seed extract was characterized through phytochemical analysis, GC-MS testing, and antioxidant activity assays. Optimization results indicated the best conditions were achieved with 200 g of sample, 1,000 mL of solvent, and 36 hours of extraction, yielding antioxidant activity with an IC₅₀ value of 18.5 ppm. Phytochemical tests identified the presence of phenolics, flavonoids, terpenoids, steroids, and saponins. The extract with the highest antioxidant activity was subsequently formulated into antioxidant transparent solid soap. Characterization of the transparent soap formulated with nyamplung seed oil showed a pH of 10.53, which remains within the safe range for alkali-based soaps. The measured moisture content was 15.05%, indicating good physical stability and a low risk of microbial growth. Furthermore, skin irritation tests revealed no signs of redness, itching, or allergic reactions, confirming that the soap is safe for human skin.